(untitled) (Research, Society and Development, 2020)
This study presents the view of health professionals regarding the use and meaning of terms, and diagnosis of “Learning Disabilities and Disorders”. The research carried out in this study is a survey. The research was conducted in four stages: (1) elaboration of a questionnaire on the theme “Learning Difficulty and Disorders”; (2) Computerization of the questionnaire through the Google Forms tool; (3) Online data collection; (4) Data Analysis. The results indicate that most professionals know how to differentiate the meaning of the terms "difficulty" and "learning disorder", this demonstrates the importance of the understanding of learning in a broader way by professionals dedicated to care and monitoring of children in the health area, as well as in the educational field. Therefore, it is necessary that the professional has sensitivity and knowledge to meet the demands that come from the school context to health services. It is important to point out the fundamental importance of the health professional to know if the difficulties presented by the students through an evaluation process are of extrinsic or intrinsic origin, so that they can elaborate a therapeutic planning appropriate to each situation and obtain results. positive during treatment.